Combined Parallel and Partial Fourier MR Reconstruction for Accelerated 8-Channel Hyperpolarized Carbon-13 In Vivo Magnetic Resonance Spectroscopic Imaging (MRSI) - Ohliger, Michael A. (2013)
PURPOSE: To implement and evaluate combined parallel magnetic resonance imaging (MRI) and partial Fourier acquisition and reconstruction for rapid hyperpolarized carbon-13 ((13)C) spectroscopic imaging. Short acquisition times mitigate hyperpolarized signal losses that occur due to T1 decay, metabolism, and radiofrequency (RF) saturation. Human applications additionally require rapid imaging to permit breath-holding and to minimize the effects of physiologic motion. MATERIALS AND METHODS: Numerical simulations were employed to validate and characterize the reconstruction. In vivo MR spectroscopic images were obtained from a rat following injection of hyperpolarized (13)C pyruvate using an 8-channel array of carbon-tuned receive elements. RESULTS: For small spectroscopic matrix sizes, combined parallel imaging and partial Fourier undersampling resulted primarily in decreased spatial resolution, with relatively less visible spatial aliasing. Parallel reconstruction qualitatively restored lost image detail, although some pixel spectra had persistent numerical error. With this technique, a 30 × 10 × 16 matrix of 4800 3D MR spectroscopy imaging voxels from a whole rat with isotropic 8 mm(3) resolution was acquired within 11 seconds. CONCLUSION: Parallel MRI and partial Fourier acquisitions can provide the shorter imaging times and wider spatial coverage that will be necessary as hyperpolarized (13)C techniques move toward human clinical applications.